SISTEM PENGENDALIAN INTERNAL PENERIMAAN KAS (Studi Kasus Pada Cv Sekartika Jati Rencana) - Hilaatul Mila Kusnia; Achmad Syaiful Hidayat Anwar; Mudrifah Mudrifah (Universitas Muhammadiyah Malang, 2020)
The aim of this study was to assess the effectiveness of the internal cash control system conducted by CV Sekartika Jati Rencana. Internal control system is a procedure used by management as a monitoring tool that every policy has been carried out by all employees. The internal control system of cash receipts is used to maintain the company's wealth, especially cash. This study analyzes the internal control system of cash receipts applied by CV Sekartika Jati Rencana and compared with the theory of internal control systems proposed by the Committee of Sponsoring Organizations (COSO). The results of this study are all internal cash control systems implemented by the CV Sekartika Jati Rencana have been effectively proven by the form that has been numbered printed, each sales document has been printed in duplicate and checking periodically. But there are some internal control systems for cash receipts that are still not effective